Análise da equiparação salarial no trabalho artístico do ator a partir da fenomenologia dos fatos jurídicos - Nakamura, Miliana Sanchez (2010)
Salary parity is a legal obligation deriving from principles of equality that aims to prevent discrimination in the workplace and to get the social justice and the equality to employees. For all this, in the first moment, the salary parity rule is applied indiscriminately to all employees. This work analyzes the world of actor s artistic job, with all related facts in this job, using the phenomenology theory of legal facts for checking if in this case there is phatic support when the work of one actor is comparable with the work of another actor. The phenomenology theory of legal facts has been applied to the analysis of salary parity in the acting industry in order to help law professionals to analyze and to understand the facts related to the world of actor s artistic job, diminishing the legal uncertainty generated by the lack of consensus regarding the matter